2019
DOI: 10.1177/0960327119871094
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxic effects and possible mechanisms of zonisamide in male rats

Abstract: Zonisamide (ZNS) is an anticonvulsant which is used to treat the symptoms of epilepsy. Although it is frequently used during reproductive ages, studies that investigated the effects of ZNS on reproductive system are limited. Therefore, we aimed to assess the effects of ZNS on male reproductive system by oral administration to rats in 25, 50, and 100 mg/kg doses for 28 days. After the exposure period, sperm concentration, motility, morphology, and DNA damage, as biomarkers of reproductive toxic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…A number of previous studies reported that antioxidants were the cellular defence mechanisms against oxidative stress and any decline in their function elevated the level of oxidative stress that led to reproduction failure (Barati et al, 2020; Martin‐Hidalgo et al, 2019). Oxidative status is reflected by the measurement of the amount of antioxidants from the sample of testes along with the MDA levels (the end‐product of lipid peroxidation) (Karaduman et al, 2019) In the current study, we found a decline of CAT activity and increase of MDA level in GTN and IM treated group of rats at all dose levels in comparison to control group that was evident of the oxidative stress in testes caused by sub‐chronic exposure of these drugs. The elevated level of the oxidative stress is testes is known to inhibit sperm production thereby causing sperm function decline.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies reported that antioxidants were the cellular defence mechanisms against oxidative stress and any decline in their function elevated the level of oxidative stress that led to reproduction failure (Barati et al, 2020; Martin‐Hidalgo et al, 2019). Oxidative status is reflected by the measurement of the amount of antioxidants from the sample of testes along with the MDA levels (the end‐product of lipid peroxidation) (Karaduman et al, 2019) In the current study, we found a decline of CAT activity and increase of MDA level in GTN and IM treated group of rats at all dose levels in comparison to control group that was evident of the oxidative stress in testes caused by sub‐chronic exposure of these drugs. The elevated level of the oxidative stress is testes is known to inhibit sperm production thereby causing sperm function decline.…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐epileptic drugs may affect the reproductive system via many different mechanisms (Herzog, 2008; Svalheim et al., 2015). Acting in the central nervous system, AEDs may alter the concentration of neurotransmitters and thus impair secretion of hormones by the hypothalamus and pituitary gland (Baysal et al., 2017; Karaduman et al., 2019). AEDs metabolised in the liver may increase catabolism of sex hormones and/or alter the level of the sex hormone‐binding globulin (SHBG), and thus affect the level of biologically active testosterone and oestradiol (Herzog, 2008; Svalheim et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AEDs metabolised in the liver may increase catabolism of sex hormones and/or alter the level of the sex hormone‐binding globulin (SHBG), and thus affect the level of biologically active testosterone and oestradiol (Herzog, 2008; Svalheim et al., 2015). Also, a direct toxic effect of AEDs on gonads is possible, as well as a direct influence on semen quality (Asadi‐Pooya et al., 2015; Baysal et al., 2017; Hamed et al., 2015; Karaduman et al., 2019; Ocek et al., 2018). It has been reported that carbamazepine, valproate and phenytoin impair the function of sperm membrane and reduce sperm motility (Semet et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged AED administration is reportedly associated with a diverse adverse effect such as behavioural/psychiatric disorders (Lee, 2019), metabolic disruption (St Louis, 2009), hepatotoxicity (Ayalew & Muche, 2018), and alterations in bone turnover markers (Arora et al., 2016) to mention but a few. Moreover, sexual dysfunction and reproductive disorders are more common among patients with epilepsy than any typical population (Atif et al., 2016; Isojärvi, 2008; Luef, 2010; Wu et al., 2018), while there are consistent pieces of evidence on the adverse effect of some AEDs particularly on the testicular dysfunction (Akinsomisoye et al., 2017; Osuntokun et al., 2017), deregulation of sex hormones (Herzog et al., 2017), reproductive toxicity (Bairy et al., 2010; Karaduman et al., 2019), and reduction of seminal quality (Falokun et al., 2010).…”
Section: Introductionmentioning
confidence: 98%